Added Value of Combined Semi-Quantitative and Visual [123I]FP-CIT SPECT Analyses for the Diagnosis of Dementia With Lewy Bodies. (February 2017) - Nicastro, Nicolas; Garibotto, Valentina; Allali, Gilles; Assal, Frederic; Burkhard, Pierre R.
Abstract : Purpose of the Report: To assess the validity of a semi-quantitative 123 I-FP-CIT SPECT method, compared to the commonly used visual analysis, in patients with probable dementia with Lewy bodies (DLB) and Alzheimer's disease (AD). We also studied DLB specific uptake impairment pattern and correlation of uptake in the presence or absence of parkinsonism. Materials and Methods: Among 1202 scans performed at our center from 2003 to 2015, we identified 93 subjects with probable DLB (mean age 76.9 ± 6.8 years, 37% women) and 18 with AD (mean age 76.9 ± 8.1 years, 50% women). Independent visual and semi-quantitative assessments based on previously established on-site reference values (including volumes-of-interest uptake, caudate-to-putamen ratio and striatal asymmetry index) were performed and compared between both groups. Results: Visual staging was considered abnormal in 96.8% of DLB patients, whereas 97.8% of subjects had an abnormal semi-quantitative assessment. Combining both methods yielded a 100% sensitivity. Patients with DLB exhibited a more pronounced impairment of putaminal uptake when associated with parkinsonism, whereas a more diffuse pattern and significantly higher uptake values were observed in the subgroup of DLB patients without parkinsonism (resp. striatal uptake 1.61 ± 0.66 vs. 2.28 ± 0.52, P = 0.01). A minority of AD subjects show minimal alterations of presynaptic dopaminergic transport (striatal uptake 3.07 ± 0.41), values being always significantly higher than those from DLB patients, irrespective of the presence of parkinsonism ( P < 0.0001) or not ( P = 0.002). Conclusions: Additional use of semi-quantitative analysis allows a higher discrimination of DLB from AD and demonstrates a specific pattern of degeneration in DLB patients according to their motor phenotype.